2022
DOI: 10.3390/cli10020012
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling Precipitation Trends in Greece since 1950s Using ERA5 Climate Reanalysis Data

Abstract: Precipitation is one of the most variable climatic parameters, as it is determined by many physical processes. The spatiotemporal characteristics of precipitation have been significantly affected by climate change during the past decades. Analysis of precipitation trends is challenging, especially in regions such as Greece, which is characterized by complex topography and includes several ungauged areas. With this study, we aim to shed new light on the climatic characteristics and inter-annual trends of precip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 72 publications
6
16
0
Order By: Relevance
“…However, no such trend appears. These results do not contradict earlier studies by Stefanidis et al [40] and Varlas et al [41], both of which found climatic fluctuations rather than linear trends. The former identified precipitation decreases in 1981-2000 and increases since 2000.…”
Section: Reanalysis Of Datasupporting
confidence: 65%
“…However, no such trend appears. These results do not contradict earlier studies by Stefanidis et al [40] and Varlas et al [41], both of which found climatic fluctuations rather than linear trends. The former identified precipitation decreases in 1981-2000 and increases since 2000.…”
Section: Reanalysis Of Datasupporting
confidence: 65%
“…A meteorological station of the National Observatory of Athens (NOA) network at Agioi Theodoroi located approximately 8 km west-southwest of Kineta recorded 206.8 mm of 2-day rainfall on 24-25 November (daily data available from 'meteo'-a Greek weather portal [91]). This precipitation amount is extreme if one considers that the annual precipitation at this area is about 400-450 mm [92]. The WRF-ARW model simulation estimated 182.6 mm of 2-day rainfall at the same area, thus agreeing very well with the measurements.…”
Section: Meteorological Analysis Of the Flash Flood Eventsupporting
confidence: 60%
“…The author estimated that the nominal power of the FPVs that can be installed in the existing 128 water reservoirs in the country, covering 10% to 30% of the water surface, varies between 4.77 GW to 14.31 GW while the annual solar electricity generation varies between 6,435.2 GWh to 19,305.6 GWh. Varlas et al [29] have reanalyzed the precipitation data in Greece since 1950s. The authors stated that the trends were characterized by nonlinearity and inter-decadal variability.…”
Section: B Floating Photovoltaics and Climate Change In Greecementioning
confidence: 99%